PEMBUATAN KEMASAN MEREK SASIRANGAN BAGI UMKM PENGRAJIN SASIRANGAN KHAS KALIMANTAN SELATAN UNTUK MENDORONG PENGEMBANGAN UMKM DI DESA SUNGAI JINGAH SEBAGAI SENTRA PRODUKSI BATIK SASIRANGAN KALIMANTAN - Yati Nurhayati; Muthia Septarina; Salamiah Salamiah (Al-Adl : Jurnal Hukum, 2017)
AbstractCommunity service aims to provide knowledge on how to make a sasirangan product packaging to create a packaging of sasirangan products that can increase the selling value and protect the brand sasirangan products at SMEs Sasirangan Banjarmasin. And provide knowledge about the importance of making sasirangan product packaging on SMEs Sasirangan Banjarmasin and Provide samples of packaging which can further be developed by business actors who join in SMEs Sasirangan Banjarmasin Community Service Activities is expected to contribute to the community sasirangan business actors, especially business actors incorporated in SMEs Sasirangan Sungai Jingah Both of theoretically and practically. The method used in the implementation of community service activities is the method of presentation, this method is used to convey to the target audience about some matters relating to the importance of benefits, packaging function of sasirangan products that can increase the sale value sasirangan, and protect the brand of sasirangan products and the next is the method of demonstration, This method is used to convey to the target audience how to manufacture the packaging of sasirangan products. The result of this Devotion is the increased awareness of the legal protection for the owner of the sasirangan brand in the Sungai Jingah sasirangan production center and understand sasirangan craftsmen in increasing the selling value through the packaging of goods.Keywords: Sasirangan, Brand, Packaging.